System and Function of Flushing in Wastewater Treatment - Radiah, Radiah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The flushing system in wastewater treatment plays a critical role in maintaining the efficiency and functionality of treatment facilities. Flushing mechanisms are employed to prevent sediment buildup, reduce blockages, and enhance the overall movement of wastewater through pipelines, tanks, and treatment units. This paper explores the various flushing techniques used in wastewater treatment, including gravity-driven, hydraulic, and mechanical flushing systems. The effectiveness of these methods is analyzed concerning factors such as flow rate, energy consumption, and environmental impact. Additionally, advanced flushing technologies, such as automated and sensor-based flushing systems, are examined for their potential in improving operational efficiency and reducing maintenance costs. The study highlights how optimized flushing mechanisms contribute to sustainable wastewater management by ensuring proper conveyance, minimizing sludge accumulation, and enhancing the performance of biological and chemical treatment processes